Can transcutaneous carbon dioxide pressure be a surrogate of blood gas samples for spontaneously breathing emergency patients? The ERNESTO experience. Issue 5 (30th December 2015) - Peschanski, Nicolas; Garcia, Léa; Delasalle, Emilie; Mzabi, Lynda; Rouff, Edwin; Dautheville, Sandrine; Renai, Fayrouz; Kieffer, Yann; Lefevre, Guillaume; Freund, Yonathan; Ray, Patrick
Abstract : Background: It is known that the arterial carbon dioxide pressure (PaCO2 ) is useful for emergency physicians to assess the severity of dyspnoeic spontaneously breathing patients. Transcutaneous carbon dioxide pressure (PtcCO2 ) measurements could be a non-invasive alternative to PaCO2 measurements obtained by blood gas samples, as suggested in previous studies. This study evaluates the reliability of a new device in the emergency department (ED). Methods: We prospectively included patients presenting to the ED with respiratory distress who were breathing spontaneously or under non-invasive ventilation. We simultaneously performed arterial blood gas measurements and measurement of PtcCO2 using a sensor placed either on the forearm or the side of the chest and connected to the TCM4 CombiM device. The agreement between PaCO2 and PtcCO2 was assessed using the Bland–Altman method. Results: Sixty-seven spontaneously breathing patients were prospectively included (mean age 70 years, 52% men) and 64 first measurements of PtcCO2 (out of 67) were analysed out of the 97 performed. Nineteen patients (28%) had pneumonia, 19 (28%) had acute heart failure and 19 (28%) had an exacerbation of chronic obstructive pulmonary disease. Mean PaCO2 was 49 mm Hg (range 22–103). The mean difference between PaCO2 and PtcCO2 was 9 mm Hg (range −47 to +54) with 95% limits of agreement of −21.8 mm Hg and 39.7 mm Hg. Only 36.3% of the measurement differences were within 5 mm Hg. Conclusions: Our results show that PtcCO2 measured by the TCM4 device could not replace PaCO2 obtained by arterial blood gas analysis.